Using lean manufacturing tools in materials supply management during the life cycle of a construction project - L. A. Oparina; E. A. Barzygin; Ya. A. Gridneva; N. S. Kasyanenko (Vestnik MGSU)
Introduction. When choosing the Engineering, Procurement, Construction (EPC) contract model, the life cycle of construction projects is managed by a specialized contractor organization. This form of construction project management is relatively new for Russian developers, and its successful implementation depends on various organizational and technical solutions, in particular, logistics management. The research problem is related to the existing risks of organizing the supply of material and technical resources during the implementation of construction projects using the EPC model, which have a negative impact on the most important indicators of construction efficiency, such as timing and cost. The paper describes strategies for preventing risk events that occur when planning the supply of material and technical resources during the life cycle of construction projects (risks of price changes, risks of violation of contractual obligations, risks of changes in the quality of delivery, reputational risks and risks of significant changes in demand). The problems of risk mitigation using lean manufacturing tools were solved.Materials and methods. The methodology and standards of project management as applied to the processes of material and technical support of construction, as well as methods of calendar-network planning, methods of project content decomposition, methods of contract strategy of construction projects implementation and elements of the methodology of package-node method of construction were used.Results. The results of the research are described and recommendations are given for the practical use of the flexible project management tool known in international practice as Just In Time.Conclusions. A justification for the use of the proposed planning tool as an activity to reduce risks associated with the supply of materials and improve the efficiency of life cycle management of construction projects is presented.